Global Health and Emergency Care: A Resuscitation Research Agenda—Part 1. (December 2013) - Aufderheide, Tom P.; Nolan, Jerry P.; Jacobs, Ian G.; van, Gerald; Bobrow, Bentley J.; Marshall, John; Finn, Judith; Becker, Lance B.; Bottiger, Bernd; Cameron, Peter; Drajer, Saul; Jung, Julianna J.; et al.
Abstract At the 2013 Academic Emergency Medicine global health consensus conference, a breakout session on a resuscitation research agenda was held. Two articles focusing on cardiac arrest and trauma resuscitation are the result of that discussion. This article describes the burden of disease and outcomes, issues in resuscitation research, and global trends in resuscitation research funding priorities. Globally, cardiovascular disease and trauma cause a high burden of disease that receives a disproportionately smaller research investment. International resuscitation research faces unique ethical challenges. It needs reliable baseline statistics regarding quality of care and outcomes; data linkages between providers; reliable and comparable national databases; and an effective, efficient, and sustainable resuscitation research infrastructure to advance the field. Research in resuscitation in low‐ and middle‐income countries is needed to understand the epidemiology, infrastructure and systems context, level of training needed, and potential for cost‐effective care to improve outcomes. Research is needed on low‐cost models of population‐based research, ways to disseminate information to the developing world, and finding the most cost‐effective strategies to improve outcomes.